The Story of Codex H (GA 015): Manuscript Migration and Primary Sources in Biblical Studies. - Allen, Garrick V.; Fowler, Kimberley (Journal of Biblical Literature, 2025)
This article explores the complex life and significance of Codex H (GA 015), a copy of Paul's letters in Greek preserving the earliest evidence for the Euthalian apparatus. Codex H was disassembled in the Megisti Lavra monastery on Mount Athos sometime between the tenth and thirteenth centuries and used as binding material and flyleaves in multiple other medieval manuscripts produced and restored there. Codex H's surviving folios are now held in Paris, Torino, Kyiv, Moscow, Saint Petersburg, and the Megisti Lavra. Its story highlights the ethical complexities inherent in scholarship on the New Testament's manuscripts, especially as it relates to digital tools and emerging forms of restorative textual scholarship. In order to begin to reconstruct Codex H before it was disassembled, we first work to understand its post-production life, tracing the paths its pages took in reverse chronological order, from their current holding institutions to Mount Athos. We argue that the story of Codex H is important because it helps us to understand the ways late ancient copies traversed time and space to their current forms as we encounter them today, offering new ways to think about the most primary sources of New Testament scholarship.